The Bergen and Oslo toll rings and infrastructure investment schemes - Jon Inge Lian (European Regional Science Association (ERSA), 2005)
When the toll rings around Bergen and Oslo was established in 1986 and 1990 respectively, they were part of a major scheme to speed up road investments. In Oslo twenty percent of the revenue was allocated to public transport investments. The paper studies the impact of these major investments in road and public transport infrastructure on car travel and on public transport services. The paper comprises of three parts: Firstly, it describes the important features of the schemes. Emphasis is placed on the funding mechanisms (toll ring, government co-funding) and on description of the investment packages. Secondly, the effects for public transport operations and performance are investigated. We look at developments in aggregate indicators like operating costs, travel patterns, modal split etc. It is concluded that qualitative improvements, like reserved bus lanes and fully connected metro services, have played an important role in Oslo, whereas public transport has lost ground in Bergen, mainly due to reduced subsidies. Thirdly, the effects on car travel (traffic volumes, travel times and timing) are analysed. It is concluded that the overall volume of car traffic and the traffic volume in the three broad sectors of both regions only to a minor extent is influenced by the investment program. Increase in income, labour and population is more important as explanatory factors. There is however a difference a difference in car travel growth rates between Bergen and Oslo, reflecting the greater emphasis on public transport both in investment programs and subsidy level in Oslo. In the end, effects of land use changes on car travel and the role of trunk road investments in land use changes is discussed and main findings are summed up and conclusions drawn.
Keywords: 330